Virtual Sensor For Automotive Engine To Compensate For The Map, Engine Speed Sensors Faults - Shalalfeh, Sohaub; Jaber, Ihab; Hroub, Ahmad (Palestine Polytechnic University , mechanical engineering , mechatronics, 2016)
Most of the functions of a modern car directly depend on reading sensors spread over parts of the engine to adjust the efficiency and performance of the engine.These sensors have an important piece of information for the control unit to build a signal that could control the actuator . If the MAP sensor is defectd this will affect the performance of the engine and air fuel ratio, but if the RPM sensor is defect then the vehicle and engine will not start. To solve this problem we use the virtual sensor principle. The proposed scheme assists in: Sensing of critical unmeasurable parameters like Volumetric and Combustion efficiency, developming of Virtual Sensor from manifold pressure dynamics for rotational speed sensor. Health Monitoring of the manifold pressure and crankshaft sensor. For the suggested scheme, two robust second-order sliding mode observer are employed that require two dynamic equations engine model based on inlet manifold pressure and rotational speed dynamics. The proposed methodology has the potential of online implementation on any automotive engine after minor tuning. This procedure is customized for 1.4 L gasoline engine sensors: Manifold Pressure and Crankshaft. The observer dynamic equation is simulated on matlab using simulink tools and compared with the real time response.
CD , 29332 , ميكاترونيكس 1/2016 , no of pages 66 , in the store
Keywords: Virtual Sensor; Mechatronics; Sensors Faults